Production Efficiencies of the Nigerian Agricultural Insurance Corporation (NAIC) Insured and Non-NAIC Insured Livestock Farmers in Kwara State, Nigeria - Ojetunde Babatunde Stephen; Emmanuel Egbodo Boheje Odum; Adewumi Olaniyi Matthew (Turkish Journal of Agriculture: Food Science and Technology, 2021)
This study used structured questionnaire to randomly collect data from livestock farmers insured under the NAIC scheme and their counterparts not under the NAIC scheme in Kwara State. The study comparatively examined their socio-economic characteristics and production efficiencies using The Stochastic Frontier Analysis and t-test. Results from the study showed that not enough youths participate in livestock production in the study area and it is a male dominated activity. A lot of non-beneficiaries of the NAIC intervention scheme are not members of cooperatives and losing out in the benefits of cooperative membership. The insured farmers are more efficient compared to those that were not insured with both having potentials for increasing their efficiency of production at the moment. The study therefore recommend that youths of ages 35years and below be encourage and provided some incentives to participate in livestock farming as well as women to check the gender imbalance of male dominance. Awareness of NAIC intervention schemes is created for livestock farmers who are not registered for the scheme while beneficiaries are made ambassadors of the scheme to have it promoted to non-beneficiaries. Livestock farmers that do not belong to any cooperative are recommended to form or belong to one so as to access the benefits of belonging to a cooperative group. The study also recommends that stakeholders in the Nigerian Agricultural insurance subsector develop strategies that will encourage much participation in their insurance interventions and also create more awareness among farming households to encourage participation in the program.